(-3+3/x-1/3):(1+2/5+2/3)=-5/4

(-3+3/x-1/3):(1+2/5+2/3)=-5/4

2 bình luận về “(-3+3/x-1/3):(1+2/5+2/3)=-5/4”

  1. Giải đáp:x=4
     
    Lời giải và giải thích chi tiết:
    (-3+3/x-1/3):(1+2/5+2/3)=(-5)/4
    (-3+3/x-1/3):(5/5+2/5+2/3)=(-5)/4
    (-3+3/x-1/3):(7/5+2/3)=(-5)/4
    (-3+3/x-1/3):(21/15+10/15)=(-5)/4
    (-3+3/x-1/3):31/15=(-5)/4
    -3+3/x-1/3=(-5)/4xx31/15
    -3+3/x-1/3=(-31)/12
    3/x-(3+1/3)=(-31)/12
    3/x-(9/3+1/3)=(-31)/12
    3/x-10/3=(-31)/12
    3/x=(-31)/12+10/3
    3/x=(-31)/12+40/12
    3/x=3/4
    =>x=4
    Vậy x=4
    \color{green}{\text{~Bachira~}}

    Trả lời

Viết một bình luận